Basic Approaches to Minimization of Vocabulary in Russian and European Educational Lexicography (E Conference Zone, 2022)
The article discusses the main differences in the approaches of Russian and European specialists to the choice of principles for minimizing vocabulary, determining the volume of the lexical minimum and sources for compiling it, using text corpora to identify various aspects of the USA of a word.